Call for Using Behavioral Science Theory for Design and Evaluation of Food Is Medicine Interventions: A Perspective Using a Case Study Approach - Shreela Sharma; Naomi Tice; Maha Almohamad; Deanna M. Hoelscher; Lorena Macias-Navarro; Wesley Gibson; Maria De La Cruz; Azar Gaminian; Mike Pomeroy; Esperanza Galvan; Melissa Melshenker Ackerman; Ru-Jye Chuang; et al. (Journal of Nutrition Education and Behavior, 2026)

The 4th global coral bleaching event: ushering in an era of near-annual bleaching - Blake L. Spady; William J. Skirving; Jacqueline L. De La Cour; Erick F. Geiger; Gang Liu; Ove Hoegh-Guldberg; Andrew Norrie; Scott F. Heron; Morgan W. Pomeroy; Graham Kolodziej; Kristen T. Brown; Derek P. Manzello (Coral Reefs, 2026)
Increasingly frequent marine heatwaves have escalated the prevalence and extent of mass coral bleaching events. Global-scale coral bleaching events (GCBEs) can unfold when marine heatwaves impact reefs across all tropical ocean basins within a common period. Here, we define an objective, quantifiable index to compare periods of satellite-derived coral heat stress accumulation globally from 1985 to 2025 and examine their relationship to confirmed GCBEs. We uncover an uninterrupted and ongoing period of global coral heat stress from 2018 to 2025, affecting an unprecedented 87% of reef areas globally. The average intensity has also been record-setting, with the median global heat stress accumulation on reef areas nearly 50% greater than the previous GCBE record. This has largely been driven by general ocean warming, as recent baseline global surface ocean temperatures (2019–2023) are comparable to extreme anomalous conditions observed ~ 25 years ago. The development of a strong El Niño event in 2023, superimposed upon the already anomalously warm ocean, culminated in the 4th GCBE, the most extensive and intensive on record. Qualitative observations of coral bleaching have been reported from 84 countries spanning all coral-containing ocean basins. An analysis of the extent and magnitude of heat stress suggests that bleaching may have impacted 98 of the 102 countries with coral reefs. GCBE4 (2023–present) marks a period of heat stress that is unprecedented by every investigated metric. However, global-scale coral bleaching-level heat stress has persisted for almost the entirety of the last decade, bringing many reef areas into an era of near-annual bleaching.

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Site use and connectivity of female grey seals (Halichoerus grypus) around Wales - Izzy Langley; Tobias Rosas da Costa Oliver; Lex Hiby; Thomas B. Stringell; Ceri W. Morris; Oliver O’Cadhla; Lisa Morgan; Kate Lock; Sarah Perry; Stephen Westcott; Dave Boyle; Birgitta I. Büche; et al. (Marine Biology, 2020)
Grey seals ( Halichoerus grypus ) are a qualifying feature of three special areas of conservation (SACs) in Wales, yet relatively little is known of their site use along this coastline. Since 1992, many individuals and organisations have contributed to a grey seal photographic identification database held by Natural Resources Wales, which is one of the largest and oldest of its kind, providing key information from grey seal haul-out sites around the Celtic and Irish Seas. Here, we investigated spatial connectivity of haul-out sites and fidelity of adult females to breeding sites. The minimum number of adult female grey seals using the area between 1992 and 2016 was 2688. Individual capture histories and relative spatial transition probabilities ( P ij ) between pairs of location groups were calculated. Adjacent locations were highly connected (e.g. Lleyn Peninsula and Bardsey, P ij = 0.7) but connections spanned the entire region, up to 230 km apart (e.g. Skomer and Dee Estuary, P ij = 0.004). Resights were recorded within SACs (e.g. Lleyn Peninsula and Bardsey [Lleyn Peninsula and the Sarnau SAC], P ij = 0.7), between SACs (e.g. Bardsey and Skomer [Pembrokeshire Marine], P ij = 0.03), between SACs and non-designated areas (e.g. Skerries and Bardsey, P ij = 0.09) and between sites outside any protected area (e.g. Dee Estuary and Anglesey, P ij = 0.5). While inter-annual fidelity to breeding sites was high ( P ij = 0.82–1), individual female grey seals moved throughout the region. This evidence of extensive site use beyond protected areas is important for the management and conservation of grey seals around Wales.